Pembuatan Video Pembelajaran dengan Cepat dan Menarik Menggunakan Aplikasi Easy Sketch - Sitti Inaya Masrura; Aprisal Aprisal; Sartika Arifin (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The purpose of this service activity is to produce creative and interesting mathematics learning media using easy sketch application. The subjects for this service activity are teachers who are members of the Forum MGMP Matematika wilayah II Polewali Mandar. The method in this service was training to make creative and interesting learning media in the form of videos. This service activity began with explanation of material about learning media which includes: the importance of using appropriate learning media for students, types of learning media, teacher obstacles in making creative and interesting learning media examples of IT-based learning. Furthermore, exercises were carried out to make learning videos using the easy sketch. The service team consisted of lecturers and students. Overall this service activity went well and smoothly. This was shown by the attention of the participants during the training, number of questions asked about the material, and the learning videos produced by the participants. Some participants had been able to make complete learning videos which include: learning objectives, material explanations, sample questions, and practice questions.